Plakilactones G and H from a marine sponge. Stereochemical determination of highly flexible systems by quantitative NMR-derived interproton distances combined with quantum mechanical calculations of 13C chemical shifts - Di Micco, Simone; Zampella, Angela; D’Auria, Maria Valeria; Festa, Carmen; De Marino, Simona; Riccio, Raffaele; Butts, Craig P.; Bifulco, Giuseppe (Beilstein Journal of Organic Chemistry, 2013)
In this paper the stereostructural investigation of two new oxygenated polyketides, plakilactones G and H, isolated from the marine sponge Plakinastrella mamillaris collected at Fiji Islands, is reported. The stereostructural studies began on plakilactone H by applying an integrated approach of the NOE-based protocol and quantum mechanical calculations of 13C chemical shifts. In particular, plakilactone H was used as a template to extend the application of NMR-derived interproton distances to a highly flexible molecular system with simultaneous assignment of four non-contiguous stereocenters. Chemical derivatization and quantum mechanical calculations of 13C on plakilactone G along with a plausible biogenetic interconversion between plakilactone G and plakilactone H allowed us to determine the absolute configuration in this two new oxygenated polyketides.
Keywords: chemical shift calculations; DFT; NMR spectroscopy; quantitative NOE; stereochemical determination of flexible systems